Purkinje Cell Maturation Participates in the Control of Oligodendrocyte Differentiation: Role of Sonic Hedgehog and Vitronectin - Bouslama-Oueghlani, Lamia (Public Library of Science, 2012)
Oligodendrocyte differentiation is temporally regulated during development by multiple factors. Here, we investigated whether the timing of oligodendrocyte differentiation might be controlled by neuronal differentiation in cerebellar organotypic cultures. In these cultures, the slices taken from newborn mice show very few oligodendrocytes during the first week of culture (immature slices) whereas their number increases importantly during the second week (mature slices). First, we showed that mature cerebellar slices or their conditioned media stimulated oligodendrocyte differentiation in immature slices thus demonstrating the existence of diffusible factors controlling oligodendrocyte differentiation. Using conditioned media from different models of slice culture in which the number of Purkinje cells varies drastically, we showed that the effects of these differentiating factors were proportional to the number of Purkinje cells. To identify these diffusible factors, we first performed a transcriptome analysis with an Affymetrix array for cerebellar cortex and then real-time quantitative PCR on mRNAs extracted from fluorescent flow cytometry sorted (FACS) Purkinje cells of L7-GFP transgenic mice at different ages. These analyses revealed that during postnatal maturation, Purkinje cells down-regulate Sonic Hedgehog and up-regulate vitronectin. Then, we showed that Sonic Hedgehog stimulates the proliferation of oligodendrocyte precursor cells and inhibits their differentiation. In contrast, vitronectin stimulates oligodendrocyte differentiation, whereas its inhibition with blocking antibodies abolishes the conditioned media effects. Altogether, these results suggest that Purkinje cells participate in controlling the timing of oligodendrocyte differentiation in the cerebellum through the developmentally regulated expression of diffusible molecules such as Sonic Hedgehog and vitronectin.